Piers/peers - Carr, Nicholas, 1981- (Melbourne, Australia : Published by GANGPRESS, 2016)
A selection of 35mm and medium format film photographs taken between 2014 and 2016 focusing on the people that frequent the many piers around Port Phillip Bay and Western Port Bay in Victoria, Australia. This is the first title published by Gang Press, a small independent publishing imprint from Melbourne, Australia.
Indigo printed.
Hand numbered edition of 100.
National Library's copy is no. 55/100.
Nicholas Carr is a photographer based in Melbourne, Australia.
Perfect bound.
Keywords: Piers -- Victoria -- Port Phillip Bay -- Pictorial works; Piers -- Victoria -- Western Port Bay -- Pictorial works; Tourists -- Victoria -- Pictorial works; Fishers -- Victoria -- Pictorial works; Street photography -- Victoria; Leisure -- Victoria -- Pictorial works; Photobooks; Australian